2021
DOI: 10.1111/jfbc.13612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger ( Zingiber officinale ) supplementation on oxidative stress parameters: A systematic review and meta‐analysis

Abstract: A wide variety of antioxidant properties are attributed to ginger (Zingiber officinale) and several randomized controlled trials (RCTs) have investigated the effect of ginger intake on major oxidative stress (OS) parameters. We conducted a systematic review and meta-analysis to evaluate the effects of using ginger to improve OS levels. Medline, Scopus, ISI Web of Science, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched up until March 2020 to gather RCTs that evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…In terms of antioxidant effects, low‐quality meta‐analyses indicated that ginger of the Zingiberaceae plants and the functional components of turmeric, mainly reduced malondialdehyde (MDA) and increase the level of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH‐Px) (Alizadeh et al, 2019; Jalali, Mahmoodi, Moosavian, et al, 2020; Morvaridzadeh et al, 2021; Sahebkar et al, 2015). It was not ignored that the results of two meta‐analysis which showed that Cur supplementation had no significant effect on CAT (GRADE level: very low) and total antioxidant capacity (TAC) (GRADE level: low) (Alizadeh & Kheirouri, 2019; Morvaridzadeh et al, 2021). None of the articles mentioned above reported publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of antioxidant effects, low‐quality meta‐analyses indicated that ginger of the Zingiberaceae plants and the functional components of turmeric, mainly reduced malondialdehyde (MDA) and increase the level of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH‐Px) (Alizadeh et al, 2019; Jalali, Mahmoodi, Moosavian, et al, 2020; Morvaridzadeh et al, 2021; Sahebkar et al, 2015). It was not ignored that the results of two meta‐analysis which showed that Cur supplementation had no significant effect on CAT (GRADE level: very low) and total antioxidant capacity (TAC) (GRADE level: low) (Alizadeh & Kheirouri, 2019; Morvaridzadeh et al, 2021). None of the articles mentioned above reported publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…c Fixed-effects model. d Egger's regression test p-value.peroxidase (GSH-Px)(Alizadeh et al, 2019;Morvaridzadeh et al, 2021;Sahebkar et al, 2015). It was not ignored that the results of two meta-analysis which showed that Cur supplementation had no significant effect on CAT (GRADE level: very low) and total antioxidant capacity (TAC) (GRADE level: low) (Alizadeh & Kheirouri, 2019; Morvaridzadeh3.4 | Osteoarthritis and pain managementOur analysis found that Zingiberaceae plants, especially ginger, have a positive effect on knee osteoarthritis (Araya-Quintanilla et al, 2020;T A B L E 5Abbreviations: CI, confidence interval; cont, control; Cur, curcumin; int, intervention; IBS, irritable bowel syndrome; MA, meta-analysis; NA, not available; OR, odds ratio; RCT, randomized controlled trial; RR, relative risk; SMD, standardized mean difference; UC, ulcerative colitis.a Total participants.…”
mentioning
confidence: 99%
“…Most Chinese herbs present in SSY, including Panax ginseng [20], Folium perillae [21], Pueraria lobata [22], Poria cocos [23], Fructus aurantii [24], Platycodon grandi orum [25], pericarpium citri reticulatae [26], Glycyrrhiza uralensis sch [27], Costus root [28], Zingiber O cinale Radix [29] and Zizyphi fructus [30], have shown anti-in ammatory and/or anti-oxidative effects. Additionally, Peucedani radix, another component of SSY, exhibits a wide spectrum of pharmacological activities including anti-infective, antitussive, anti-asthmatic and expectorant effects, which help relieve symptoms and improve ALI prognosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…The high pharmacological potential of medicinal herbs as natural antioxidative and anti-inflammation agents suggests using these additives to relieve the impacts of herbicides, insecticides, and pesticides on aquatic animals (Sinha et al 2021;Yousefi et al 2021). Zingiber officinale or ginger is a natural medicinal plant with high bioactive properties (Morvaridzadeh et al 2020(Morvaridzadeh et al , 2021. The dietary inclusion of ginger led to marked enhancement in the growth performance, intestinal health, digestion capacity, antioxidative, and immune responses of several fish species (Chung et al 2021b;Fazelan et al 2020;Korni and Khalil 2017).…”
Section: Introductionmentioning
confidence: 99%